EKSISTENSI MAJALAH BERBAHASA SUNDA MANGLE DI ERA REVOLUSI INDUSTRI 4.0 - Roni Tabroni; Nunung Sanusi (Ilmu Komunikasi, FISIP Universitas Pasundan, 2020)
ABSTRACT Of the various sectors of community life that were affected by the influence of the Industrial Revolution 4.0, the mass media industry can be assumed to be the most affected. Mangle Magazine is a magazine that is still consistent until the time of publication one in a week. This study aims to find and describe the editorial and advertising management strategies undertaken by Mangle so that they can be consistently published to date. The research method used rests on a qualitative paradigm with tradition used as a case study. The results showed that for editorial policy, Mangle retained its positioning as a “panglipu”r media (entertaining) but still provided social criticism through the rubric of “carpon” (short stories) and still retained its distinctive characteristic of using the Sundanese language. In addition, Mangle also emphasized in accordance with its meaning, to always present a female figure in every magazine cover. While the business strategy, Mangle cooperates with various agencies ranging from the Regional Government, Service, to Higher Education, to subscribe to Mangle magazine, while continuing to receive advertisements from other parties as a source of business income. This cooperation is part of the hallmark of competencies that must be had in the industrial revolution era 4.0, namely collaboration.